2022
DOI: 10.24840/2183-6493_008.001_0007
|View full text |Cite
|
Sign up to set email alerts
|

Intelligence, Beliefs on IQ and Learning Style predict Academic Performance in Mechanical Engineering Students

Abstract: In this study we aimed to investigate whether beliefs on intelligence, intelligence quotient, and learning styles predict academic performance among students in mechanical engineering. For this purpose, forty-two students from the Department of Mechanical Engineering of the University of Porto were recruited among the available population. Participants responded to the measurement of this study via a Google form and on a voluntary basis. To investigate our hypothesis, beliefs on intelligence inventory, learnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
(35 reference statements)
1
0
0
Order By: Relevance
“…The present study found no significant association of IQ with academic performance (p = 0.584), which agrees with earlier reports [22][23][24]. On the contrary, other studies suggested a positive influence of IQ on the students' academic achievement [25,26].…”
Section: Discussionsupporting
confidence: 90%
“…The present study found no significant association of IQ with academic performance (p = 0.584), which agrees with earlier reports [22][23][24]. On the contrary, other studies suggested a positive influence of IQ on the students' academic achievement [25,26].…”
Section: Discussionsupporting
confidence: 90%